Whose science? Whose knowledge? : thinking from women's lives - Harding, Sandra G. (The science question in feminism, 1991)
"With a book that is guaranteed to upset familiar assumptions about or ways of knowing, Sandra Harding again steps into the center of a thorn debate -- a debate about the nature of the scientific enterprise and of human knowledge itself. Vigorously and persuasively, she develops further the themes first addressed in The Science Question in Feminism. It that widely influential book, she asked what it is that is distinctive about feminist research. Here she conducts a compelling analysis of feminist theories on the philosophical problem of how we know what we know."--Back cover